Waste SMD LEDs from End-of-Life Residential LED Lamps: Presence and Characterisation of Rare Earth Elements and Precious Metals as a Function of Correlated Colour Temperature - Konstantinos M. Sideris; Ioannis Katsiris; Dimitrios Fragkoulis; Vassilis N. Stathopoulos; Panagiotis Sinioros (Recycling)
Energy consumption in buildings is linked to lighting technology. Light-emitting diode (LED) technology includes lamps and luminaires for general lighting applications. Due to their structure, LED lamps are expected to generate specific waste electrical and electronic equipment (WEEE) streams. LEDs are the main source of luminous flux, and their elemental composition is of particular interest to the recycling sector. In this study, surface-mount device (SMD) LEDs from six types of LED lamps (E27, E14, G9, R7S, GU10, and MR16) were removed, collected, separated by correlated colour temperature (CCT) (2700 K, 3000 K, 4000 K, and 6500 K), and characterised for the presence of rare earth elements and precious metals. They were digested with HNO3, aqua regia, and HF in a hot plate and characterised by inductively coupled plasma mass spectrometry (ICP-MS). The concentration of each element as a function of CCT ranged as follows: lanthanum, 242–1840 mg/kg; cerium, 132–284 mg/kg; europium, 15–69 mg/kg; gadolinium, 1.9–3.8 mg/kg; terbium, 0.1–0.4 mg/kg; lutetium, 29–6381 mg/kg; yttrium, 4804–11,551 mg/kg; silver, 2712–5262 mg/kg; gold, 502–956 mg/kg; and palladium, 32–110 mg/kg. These results indicate the need for selective removal and separate recycling processes of SMD LEDs from LED lamps.